An Approach for Efficient Heat Source Selection in Long-Term Expansion Planning of Urban District Heating Systems - Edeleva Olga; Mikheev Alexei; Stennikov Valery (E3S Web of Conferences, 2023)
This study proposes an approach to selecting efficient heat sources in the context of long-term expansion planning for urban district heating systems. The approach includes two stages: synthesis and optimization. During the synthesis stage, potential heat source structures are generated using graph grammars. In the optimization stage, the most effective combination of heat source equipment is selected based on minimum construction costs, heat network costs, and pollutant emissions fees. Iterative linking of these two stages provides a coherent solution for determining the structure and parameters of heat sources, for streamlining the process of performing computational studies. The proposed approach is a comprehensive and cost-effective method for selecting heat source structures for urban district heating systems.